THE ROLE OF LEADERSHIP IN DESIGN MANAGEMENT: A CASE STUDY OF JEPARA CARVING FURNITURE INDUSTRY - Mutiara, Maitri Widya; Tunjungsari, Hetty Karunia (International Journal of Application on Economics and Business, 2025)
Leadership in design management plays a crucial role in the furniture industry, especially in Jepara, which is known for its unique traditional carving art. This study examines how leadership roles at various levels of management contribute to the successful implementation of design management in the carved furniture industry. Through a case study approach with a qualitative method, this study analyses leadership practices in design management in several Jepara furniture companies, with the focus on PT Els Artsindo as an example of effective implementation. The results show that effective leadership in design management requires an integration between strategic vision, coordination skills, and a deep understanding of local values. At the top management level, leaders play a role in determining the strategic direction and ensuring alignment between design and business goals. At the intermediate level, design managers serve as a bridge between strategic vision and implementation, coordinating various divisions and ensuring design quality. While at the operational level, leadership focuses on product execution and quality control. Case studies show that the success of design management in the Jepara furniture industry depends on the ability of leaders to balance the demands of the modern market with the preservation of traditional carving values. Effective leaders can integrate designers, carving craftsmen, and production teams into creating products that have added value and competitiveness. This research contributes to understanding how leadership in design management can support the development of the traditional furniture industry in the modern era, while providing practical implications for the development of leadership models in the creative industry.